2018
DOI: 10.1186/s13195-018-0417-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio in dementia with Lewy bodies balanced between Alzheimer’s disease and Parkinson’s disease dementia: a cross-sectional study

Abstract: BackgroundGender distribution varies across neurodegenerative disorders, with, traditionally, a higher female frequency reported in Alzheimer’s disease (AD) and a higher male frequency in Parkinson’s disease (PD). Conflicting results on gender distribution are reported concerning dementia with Lewy bodies (DLB), usually considered as an intermediate disease between AD and PD. The aim of the present study was to investigate gender differences in DLB in French specialized memory settings using data from the Fren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 32 publications
1
34
0
1
Order By: Relevance
“…In addition to maltose, network analyses suggested a role for androgenic steroid metabolites in global cognition. Sex differences in cognitive function and certain neuropsychiatric diseases have been reported previously [1921]. Consistent with findings reported here, sex hormones, including androgens, were believed to be important drivers underlying these associations [20,22].…”
Section: Discussionsupporting
confidence: 90%
“…In addition to maltose, network analyses suggested a role for androgenic steroid metabolites in global cognition. Sex differences in cognitive function and certain neuropsychiatric diseases have been reported previously [1921]. Consistent with findings reported here, sex hormones, including androgens, were believed to be important drivers underlying these associations [20,22].…”
Section: Discussionsupporting
confidence: 90%
“…In line with this hypothesis, a recent study reported a higher DLB prevalence of men than women under the age of 75 years, which equalized between the ages of 75 and 80 years. Above the age of 80 years, however, DLB was more common in women [8]. Future studies will have to demonstrate whether this shift in prevalence is mediated by hormonal differences.…”
Section: Discussionmentioning
confidence: 93%
“…Pathologically, DLB is characterized by the presence of cortical Lewy bodies, i.e., neuronal inclusions of alpha-synuclein proteins [2], frequently combined with Alzheimer's disease (AD) pathology, i.e., amyloid plaques and neurofibrillary tangles (NFT) [3]. Most studies report a higher prevalence of DLB in men than in women [4][5][6][7], although a few report the opposite [8,9]. In addition to the skewed distribution, there is evidence of differences in the underlying pathology between women and men with DLB.…”
Section: Introductionmentioning
confidence: 99%
“…Males have approximately four times the incidence rate of DLB compared to females [Savica et al, 2013], though visual hallucinations are reportedly more common in females [Chiu et al, 2018], particularly at older ages and in the context of more severe neuropsychiatric symptoms. Recent work suggests that DLB is more prevalent in females than males after age 75, which may reflect a survival bias [Mouton et al, 2018]. Sex differences have been less frequently studied in DLB than other LBDs.…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 99%